UASB-septic tank as an alternative for decentralized wastewater treatment in Mexico. Issue 14 (20th June 2019) - Santiago-Díaz, Ángel L.; García-Albortante, Julisa; Salazar-Peláez, Mónica L.
ABSTRACT: The aim of this work was to evaluate the performance of a UASB-septic tank as a decentralized treatment of high-strength municipal wastewater under two different HRTs (48 and 72 h). Thus, a lab-scale (44.85 L) UASB-septic tank constituted by three compartments was operated under HRT 72 and 48 h. Removal efficiencies of total chemical oxygen demand (COD), biological oxygen demand (BOD5 ) and suspended solids (SS) ranged from 60% to 80% for the first two parameters and from 70% to 90% for the last one. According to the statistical analysis, it was established that decreasing HRT from 72 to 48 h did not affect the performance of the UASB-septic tank; therefore, the latter HRT is recommended to be used for operation. In the first compartment, most of the organic matter removal was carried out, while the other two compartments served as polishing. Over the course of six months, the VS concentration and VS/TS ratio in sludge blanket decreased, indicating digestion and stabilization of the retained solids. Also, an increase of 4% in sludge volume was observed; thus, time for desludging would be approximately five years. Comparison of the UASB-septic tank and the UASB reactor showed that both systems had similar performance regarding effluent concentrations of organic matter and solids. Thus, under low volumetric organic load conditions (less than 20 mg COD/L h), the former is an attractive option for municipal wastewater treatment.